This equation is causing a headache. How can I solve it when it has two equal signs in it?

sqrt (x ^ 2 - 49) = sqrt (x ^ 2 - 49) = sqrt (x-7)

Never mind I just saw the folly of my ways. Just from typing this out it helped.

Thanks for being here!

This equation is causing a headache. How can I solve it when it has two equal signs in it?

sqrt (x ^ 2 - 49) = sqrt (x ^ 2 - 49) = sqrt (x-7)

Never mind I just saw the folly of my ways. Just from typing this out it helped.

Thanks for being here!

sqrt (x ^ 2 - 49) = sqrt (x ^ 2 - 49) = sqrt (x-7)

Never mind I just saw the folly of my ways. Just from typing this out it helped.

Thanks for being here!

- stapel_eliz
**Posts:**1731**Joined:**Mon Dec 08, 2008 4:22 pm-
**Contact:**

mamanana wrote:This equation is causing a headache. How can I solve it when it has two equal signs in it?

sqrt (x ^ 2 - 49) = sqrt (x ^ 2 - 49) = sqrt (x-7)

I don't know what the point of the first square root and "equals" sign is, because it's just repeated information.

Solve the equation created by the second and third radicals